Linkage to HIV Care Following HIV Self‑testing Among Men: Systematic Review of Quantitative and Qualitative Studies from Six Countries in Sub‑Saharan Africa - Hlongwa, Mbuzeleni; Hlongwana, Khumbulani; Makhunga, Sizwe; Choko, Augustine T.; Dzinamarira, Tafadzwa; Conserve, Donaldson; Tsai, Alexander C. (AIDS and Behavior, 2023)
Gender disparities are pervasive throughout the HIV care continuum in sub-Saharan Africa, with men testing, receiving treatment, and achieving viral suppression at lower rates, and experiencing mortality at higher rates, compared with women. HIV self-testing (HIVST) has been shown to be highly acceptable among men in sub-Saharan Africa. However, evidence on linkage to HIV care following a reactive HIVST result is limited. In this systematic review, we aimed to synthesize the quantitative and qualitative literature from sub-Saharan Africa on men’s rates of linkage to HIV care after receiving a reactive HIVST result. We systematically searched 14 bibliometric databases. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) flow diagram was used to document the screening results. The Mixed Methods Appraisal Tool (MMAT) was used to assess the methodological quality of the included studies. Of 22,446 references screened, 15 articles were eligible for inclusion in this review. Linkage to HIV care following a reactive HIVST result was subject to several barriers: financial constraints due to travelling costs, potential long waiting hours at the clinics, stigma, discrimination, and privacy concerns. Men’s rates of seeking confirmatory testing and linking to HIV care following a reactive HIVST result were inconsistent across studies. Combining financial incentives with HIVST was found to increase the likelihood of linking to HIV care following a reactive HIVST result. The variable rates of linkage to HIV care following a reactive HIVST result suggest a need for further research and development into strategies to increase linkage to HIV care.
Keywords: HIV testing; HIV self-testing; Linkage to care; Men; Stigma; Sub-Saharan Africa